MANAGEMENT OF ENVIRONMENTAL ETHICS APPROACH TO STUDENTS - Andrasmoro, Dony (Journal of Geography Science and Education, 2019)
The purpose of this study was to determine the role of students in the level of awareness of environmental phenomena at the IKIP PGRI Pontianak Campus. the aim of building student awareness about the environment through Population and Environmental Education (PKLH) courses to support sustainable development. this research method is descriptive qualitative with the knowledge triangle learning approach based on interactive discussion analysis of knowledge, education and environmental innovation. the results of research by utilizing interactive discussion methods can encourage changes in students' attitudes to be orderly and respect environmental aspects by strengthening environmental ethics. The results of the learning analysis study were conducted using an out class teaching system. managing the results of the implementation of case studies and the reality of the results of theoretical studies that are implemented against the phenomenon of potential environmental problems. out class implementation building eduction of disaster mitigation management to environmental problems that focus on the phenomenon of inorganic waste. the role of the results of the study of strengthening environmental ethics in supporting student awareness with management efforts oriented towards economic, social and environmental approaches based on sustainable development. Keywords: Ethics, Environment, Students.